A flexible artificial intrinsic-synaptic tactile sensory organ - Yu Rim Lee (Nature Portfolio, 2020)
Emulating the preprocessing abilities of sensory organs and sensory memory at the device level remains a challenge. Here, the authors demonstrate a flexible tactile sensor based on barium titanate nanoparticles in ferroelectric nanocomposite capable of emulating filtering and sensory memory functions.